1996
DOI: 10.1017/s0952675700002098
|View full text |Cite
|
Sign up to set email alerts
|

Final Lowering in Kipare

Abstract: In many languages, fundamental frequency shows a marked decrease utterance-finally or phrase-finally. Ladefoged (1982) generalises that ‘in nearly all languages the completion of a grammatical unit such as a normal sentence is signaled by a falling pitch’. Bolinger (1978) also writes that ‘the most widely diffused intonational phenomenon seems to be the tendency to “go down at the end”’. These sorts of abrupt decreases which affect only the end of the utterance (known as FINAL LOWERING) are distinct from gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 17 publications
(21 reference statements)
2
24
0
Order By: Relevance
“…The reduced pitch range associated with lesser vocal effort, then, signals lesser speaker involvment or emotional disengagement. Previous studies have documented the manipulation of global pitch range as a linguistic device to differentiate such meanings as the "incredulity" versus the "uncertainty" interpretation of contour type 2 of our first corpus [16] and incredulous rhetorical versus unmarked yes-no question intrepretations of sentence final rising configurations [8,17]. Our results suggest that final lowering is a shorter term use of this same device.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The reduced pitch range associated with lesser vocal effort, then, signals lesser speaker involvment or emotional disengagement. Previous studies have documented the manipulation of global pitch range as a linguistic device to differentiate such meanings as the "incredulity" versus the "uncertainty" interpretation of contour type 2 of our first corpus [16] and incredulous rhetorical versus unmarked yes-no question intrepretations of sentence final rising configurations [8,17]. Our results suggest that final lowering is a shorter term use of this same device.…”
Section: Resultssupporting
confidence: 58%
“…One component of the downtrend that has been identified in this way is "final lowering", a decline in backdrop pitch range for the last few centiseconds of declaratives [6,7,8], with more drastic decline indicating a stronger discourse disjuncture [9,10]. Given its apparent connection to declarative intonations and the discourse function of indicating topic finality, it seems plausible to think of final lowering as a linguistically meaningful "fade-out" -i.e., a somewhat shorter-term version of the change in global F0 level that occurs when the talker manipulates overall loudness.…”
Section: Introductionmentioning
confidence: 99%
“…Hirschberg and Ward [1992, p. 250] showed that pitch range plays the largest role in interpreting the rise-fall-rise contour (L* ϩ H L H% in ToBI's transcription), with larger pitch ranges indicating incredulity and smaller ones indicating uncertainty. Herman [1996] reported that in Kipare (a Bantu tone language), statements are signalled by nonexpanded pitch range with final lowering, yes/no questions by expanded pitch range with final lowering, and incredulous questions by expanded pitch range with final raising. Jun and Oh [1996] suggested that for some Korean speakers, incredulity questions (echo questions expressing incredulity) are distinguished from wh-questions by a larger pitch range, higher amplitude, and boundary tones.…”
Section: Introductionmentioning
confidence: 99%
“…Another support is its connection with dec1aratives. In Kipare, fmal lowering was found absent in sentences meant to show incredulity [12]. The third is its potential link to focus encoding, more specifically, the post focus compression [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Final lowering, indicating an additional lowering near the end of the utterance, has been found in a variety of languages with very different prosodic systems, such as English [1-3], Greek [2], Danish [4], Dutch [5], Yoruba [6,7], Spanish [8], German [9], Japanese [10,11], Kipare [12] and Chinese [13]. Despite the discovery of final lowering effect in widespread languages, it still remains disputable whether its origin is physiological, phonological or paralinguistic.…”
Section: Introductionmentioning
confidence: 99%